(untitled) (Journal of Pharmaceutical Negative Results, 2023)
An conventional and mainstream medical system called Ayurveda has been a wellspring of innovative ideas and medical supplies. According to the literature, Euphorbia hirta Linn. (EH) is a medicinal herb that has been advantageously verified. Different components of this plant are used by India's rural and tribal populations to treat a variety of illnesses. By researching the plant's pharmacology in vitro and in vivo, its use in conventional medicine has been established scientifically. Multiple data base resources were used to collect the data.